Pancreatic Extragastrointestinal Stromal Tumors, Interstitial Cajal Like Cells, and Telocytes - Padhi, Somanath; Sarangi, Rajlaxmi; Mallick, Saumyaranjan (JOP. Journal of the Pancreas, 2013)
Context The discovery and subsequent ultrastructural characterization of the interstitial Cajal like cells (now called telocytes) in virtually every anatomic sites of the human body, by Laurentiu M Popescu and co-workers, have dramatically improved the understanding the function of these cells and pathogenesis of extragastrointestinal stromal tumors (EGIST). Pancreatic extragastrointestinal stromal tumors (pEGIST), phenotypically similar to pancreatic interstitial Cajal like cells, are extremely rare with an unpredictable biological behavior. Objective To review the clinicopathological, radiological, immunohistochemical, and therapeutic outcome data of all reported cases of pEGIST, and highlight the developments in the field of pancreatic interstitial Cajal like cells/telocytes. Methods A systematic review of English literature (January 2000 to July 2012) was done by using the search engine of PubMed, PubMed Central, Google Scholar, and the Directory of Open Access Journals. Results There have been 19 reported cases of pEGIST during the last decade, over an age range of 31 to 84 years (mean: 56 years) with equal gender predilection ((male:female ratio: 9:10). Preoperative radiological characteristics have been mostly nondiagnostic though these were used, in some, for tissue diagnosis. Majority of pEGIST were localized to pancreatic head (8/19, 42.1%), and 15 of 19 patients (78.9%) were symptomatic at first presentation. The mean size ranged from 2.5 to 35cm (mean: 14 cm). Histomorphological features were that of predominantly spindle cell tumor which consistently expressed c-KIT/CD117 and CD34 by immunohistochemistry, making these two as the most sensitive markers at this site. Results from studies involving discovery on gastrointestinal stromal tumor 1 (DOG-1), the most specific biomarker of GIST/EGIST, has been inconclusive and this was found to be positive in one case only. Neoadjuvant chemotherapy with imatinib mesylate and sunitinib were used in few cases, and genetic analysis of c-KIT proto-oncogene was done in two. By univariate analysis, none of the clinicopathological parameters, except surgical resection with microscopic free margin (R0 resection) (P<0.05), were found to be an important indicators of outcome. Conclusion The biological behavior of pEGIST, at present, seems unpredictable which requires indefinite period of follow-up. Large number of such cases with genetic analysis supplemented with immunohistochemistry studies will hopefully throw more light in these tumors. Image: Gross specimen showing a large lobulated tumor in relation to the body and tail of the pancreas.